PENGARUH LAMA PENYIMPANAN PADA LEMARI ES TERHADAP JUMLAH BAKTERI SUSU SGM SEBAGAI SUMBER NUTRISI ANAK - Fitria, Davina; Advinda, Linda (Universitas Cokroaminoto Palopo, 2025)
Milk is one of the main sources of nutrition for children's growth and development. The quality of milk consumed plays an important role in ensuring that children receive adequate nutrition to maintain their health. One of the efforts of consumers to stop the development of microorganisms and maintain milk quality is to store milk in the refrigerator. The purpose of the study was to examine the effect of the length of storage of SGM formula (0-6 Months) in the refrigerator on the number of bacteria contained in it. The research design was a completely randomized design (CRD) with 6 treatments, namely 0, 1, 2, 3, 4, and 5 days of storage, replicated 3 times. The resulting data were analyzed statistically using Anova and Duncan's Multiple Range Test (DMRT). That Day 5, Day 4, and Day 2 had no significant difference in bacterial counts as they had the same notation 'a'. In contrast, Day 1 and Control, which had the notation 'b', were significantly different from the 'a' group, while Day 3 showed marginal differences with both groups